Multiple geographies of precarity: Accommodation policies for asylum seekers in metropolitan Athens, Greece. (April 2022) - Papatzani, Eva (Evangelia); Psallidaki, Timokleia; Kandylis, George; Micha, Irini
Since early 2016, in the context of the so-called 'refugee crisis', a series of accommodation policies for asylum seekers were developed in Greece under the regime of 'emergency', consisting of two pillars: on the one hand, the 'campisation' of accommodation in the mainland and, on the other hand, urban apartments. This article sheds light on the uneven geographies of accommodation policies for asylum seekers in metropolitan Athens, by investigating in a complementary way the aforementioned distinct – yet intertwined – types of accommodation. Through the lens of 'precarity of place', it argues that asylum accommodation in Athens reproduces multiple geographies of precarity through (a) filtering mechanisms based mainly on vulnerability categorisations, (b) socio-spatial isolation and segregation, and (c) a no-choice basis and extensive control of everyday habitation. The article explores the impact of the above on the everyday lives, socio-spatial relationships, and processes of belonging of asylum seekers, as well as on how they experience – and sometimes contest – precarity of place. The research, conducted in metropolitan Athens, is based on a mixed-methods approach that includes critical policy analysis and interviews with asylum seekers accommodated in camps and apartments, and representatives of institutional actors involved in the accommodation sector.